2000
DOI: 10.1007/bf02682087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polychromatic polarized light on afferent traffic in skin branches of somatic nerves

Abstract: Short-term irradiation of rat hind limb with polychromatic polarized light at 400-2000 nm produces a long-term inhibition of baseline afferent traffic in n. saphenus, while nonpolarized light produces biphasic changes in baseline activity: transient activation is followed by long-term inhibition of discharges in the nerve. Subcutaneous injection of sodium nitroprusside (10 microg/ml) with subsequent irradiation of the hind limb with polarized light significantly increased afferent activity in the sciatic nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Chumak et al 8 found that irradiation of rat hind limb with polychromatic polarized light at 400-2000 nm produced a longterm inhibition of baseline afferent traffic in the saphenous nerve, while nonpolarized light produced biphasic changes in baseline activity. Ribeiro et al 9 investigated the healing of burns in rats by irradiating the lesions with a linearly polarized He-Ne laser beam parallel to the spinal column of the rat, or using the same laser and dose, but aligning the light polarization perpendicularly to the relative orientation of the spinal column.…”
Section: Introductionmentioning
confidence: 99%
“…Chumak et al 8 found that irradiation of rat hind limb with polychromatic polarized light at 400-2000 nm produced a longterm inhibition of baseline afferent traffic in the saphenous nerve, while nonpolarized light produced biphasic changes in baseline activity. Ribeiro et al 9 investigated the healing of burns in rats by irradiating the lesions with a linearly polarized He-Ne laser beam parallel to the spinal column of the rat, or using the same laser and dose, but aligning the light polarization perpendicularly to the relative orientation of the spinal column.…”
Section: Introductionmentioning
confidence: 99%